2021
DOI: 10.1016/j.jbc.2021.101372
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic transcription factor REST upregulates glutamate transporter EAAT2, protecting dopaminergic neurons from manganese-induced excitotoxicity

Abstract: Chronic exposure to high levels of manganese (Mn) leads to manganism, a neurological disorder with similar symptoms to those inherent to Parkinson's disease. However, the underlying mechanisms of this pathological condition have yet to be established. Since the human excitatory amino acid transporter 2 (EAAT2) (glutamate transporter 1 in rodents) is predominantly expressed in astrocytes and its dysregulation is involved in Mn-induced excitotoxic neuronal injury, characterization of the mechanisms that mediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 77 publications
3
23
0
Order By: Relevance
“…Mn toxicity in the striatum is associated with glutamate excitotoxicity (Brouillet et al, 1993) and decreased in GLT‐1 mRNA and protein levels in the mouse brain (Johnson Jr. et al, 2018; Pajarillo et al, 2018). Since REST modulates astrocytic EAAT2 (GLT‐1) (Pajarillo, Digman, et al, 2021), we determined if modulation of REST affects GLT‐1 (EAAT2) expression in the mouse brain. The results showed that Mn decreased GLT‐1 mRNA and protein levels in the striatum of mice infused with the control vectors of AAV5‐GFAP‐GFP (Figure 8a,b), and striatal astrocytic REST deletion by infusion of the AAV5‐GFAP‐Cre‐GFP vectors further exacerbated the Mn‐induced decrease in GLT‐1 mRNA and protein levels in the striatum.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Mn toxicity in the striatum is associated with glutamate excitotoxicity (Brouillet et al, 1993) and decreased in GLT‐1 mRNA and protein levels in the mouse brain (Johnson Jr. et al, 2018; Pajarillo et al, 2018). Since REST modulates astrocytic EAAT2 (GLT‐1) (Pajarillo, Digman, et al, 2021), we determined if modulation of REST affects GLT‐1 (EAAT2) expression in the mouse brain. The results showed that Mn decreased GLT‐1 mRNA and protein levels in the striatum of mice infused with the control vectors of AAV5‐GFAP‐GFP (Figure 8a,b), and striatal astrocytic REST deletion by infusion of the AAV5‐GFAP‐Cre‐GFP vectors further exacerbated the Mn‐induced decrease in GLT‐1 mRNA and protein levels in the striatum.…”
Section: Resultsmentioning
confidence: 99%
“…Empty vectors served as control. Briefly, PHA were transfected with EV (pCMV6‐entry and TetO‐FUW) and plasmid DNA vectors for REST, or DN‐REST by electroporation and incubated for 48 h as described in our previous studies (Pajarillo, Digman, et al, 2021). After incubation, REST or DN‐REST‐overexpressing PHA were exposed to Mn (250 μM, 6 h), followed by replacement of the Mn‐containing media with fresh experimental media for an additional of 6 h. Next, the PHA‐CM was applied to LUHMES cells to test the effects of astrocytic REST on dopaminergic neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations